2019
DOI: 10.1002/jsde.12304
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cloud Point Curves of Alkyl Ethoxylates with the Hydrophilic–Lipophilic‐Difference and Net‐Average‐Curvature (HLD‐NAC) Framework

Abstract: Understanding and predicting cloud point phenomena is important for the formulation of nonionic surfactant systems, and the design of cloud‐phenomena‐associated separation processes. There have been several approaches to fit and predict the cloud point phenomena, in most cases using bulk thermodynamic approaches. In this work, we introduced the hydrophilic–lipophilic‐difference and net‐average‐curvature (HLD‐NAC) as an interfacial (curvature) approach to predict cloud point values at different surfactant conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…After sealing the tubes, these tubes were mixed via gentle wrist turning 20 times until the solution was well mixed. The test tubes were then settled Note: (a) Value of EACN reported by Baran et al (1994); (b) Value of EACN reported by Choi (2020).…”
Section: Phase Behavior Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…After sealing the tubes, these tubes were mixed via gentle wrist turning 20 times until the solution was well mixed. The test tubes were then settled Note: (a) Value of EACN reported by Baran et al (1994); (b) Value of EACN reported by Choi (2020).…”
Section: Phase Behavior Studiesmentioning
confidence: 99%
“…The test tubes in Figure 6 suggest a salinity window of 9.2%-10.8% NaCl. The phase scan picture in Figure 6 was taken after 1 week of settling (Choi, 2020). The high interfacial rigidity of extended surfactants (Acosta et al, 2012) can produce metastable Type I and II μEs, and therefore, the experimental salinity window could be larger than that displayed in the picture of Figure 6 if one waited for several weeks.…”
Section: Hld-nac and Hld Bi -Nac Fits Of Phase Behavior (Salinity) Scansmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement of surfactant formulation science through the development of the HLD framework has received a high degree of attention over the past 40 years and continues to be an area of vigorous research (Acosta, 2008; Choi et al, 2019; Salager et al, 1979, 2020). This semiempirical framework focuses on surfactant‐oil–water (SOW) systems and seeks to describe the competing affinities of surfactant towards oil and towards water via a scaling that defines HLD = 0 as the condition in which surfactant affinity is exactly balanced.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the concept of HLB has been extended and refined via the introduction of the so-called HLD (hydrophilic–lipophilic difference) (Figure ). The HLD analysis takes into account not only the nature of the surfactant but also the nature of the oil itself.…”
Section: Data-driven and Semiphenomenological Modelingmentioning
confidence: 99%